Estimating emission from ships using automatic identifications system (AIS) data and analyzing uncertainty factors on emission - Li, Qingyao (2019)
This paper aims to conduct the general cargo ship emission accounting including greenhouse gas and other air pollutants in Port of Singapore, as well as discuss the external uncertainty factors and their impacts on ship emission. Among different types of vessels visiting Port of Singapore, hundreds of general cargo carriers calling at Singapore every year contribute a significant portion of pollution, which draws people’s interests to estimate the emission for the purpose of supervision and control. Currently, there are two general methods used worldwide to estimate the vessels’ emission, namely top-down and bottom-up methods. This paper reviews previous emission accounting research and uncertainty factors analysis, as well as applies bottom-up method using Automatic Identification System (AIS) data which consists of detailed satellite information of the ships to conduct emission accounting. F-test in statistics is deployed to find the effect of uncertainty factors including heavy rain and haze. ARENA simulation model is used to simulate the effect of breakdowns and typhoons. The estimation results and uncertainty analysis carried out in this paper will serve as a reference and assist the shipping companies and port authorities to supervise the emission.